Treatment of peritoneal metastases from gastric carcinoma - Polkowski Wojciech P.; Rawicz-Pruszynski Karol; Mielko Jerzy; Geca Katarzyna; Skorzewska Magdalena; Cisel Bogumila (Current Issues in Pharmacy and Medical Sciences, 2017)
Patients with advanced gastric cancer and positive peritoneal cytology and/or peritoneal dissemination are deemed to be incurable and to hold dismal prognosis. So far, the only treatment option for these patients has been palliative systemic (chemo)therapy. However, for the last three decades, great progress has been made in attempts to treat (potential) peritoneal dissemination by means of complete cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy (HIPEC) after preoperative systemic therapy. This review is focused on the recent achievements of this multimodal strategy. Additionally, the review stands as background for the 4th International Conference “Advances in Surgical Oncology” that was held at the Medical University of Lublin (Poland) in November 2017, and dedicated to cytoreductive surgery and HIPEC for advanced gastric cancer.